Characterisation And Crystallisation Of Deptor - Yeap, Kean Heng (2021)
The mechanistic target of rapamycin (mTOR) signalling pathway integrates wide varieties of nutrients to regulate important cellular processes related to cell growth. mTOR is a huge serine/threonine protein kinase and exists in two distinct complexes, mTORC1 and mTORC2. DEPTOR is an endogenous inhibitor of mTOR and consists of two DEP domains in tandem arrangement and a PDZ domain. The Escherichia coli expression system was used for cloning and expression experiments. Here, besides the full-length protein, various truncated mutants were designed as well to gain insights into the characteristics and architectures of the protein. Four truncated mutants were constructed to represent the first DEP domain (DEP1), the second DEP domain (DEP2), both DEP domains (DEP12) and the PDZ domain. DEPTOR, DEP1, DEP2 and DEP12 were expressed as soluble proteins but PDZ was insoluble.